Wide-temperature-range gel nanoparticle emulsion as well as preparation method and application thereof
By using wide-temperature domain gel nanoparticle emulsion in the battery cell, the problems of insufficient reaction and poor temperature resistance of the condensed electrolyte inside the battery cell are solved, and the high safety and low impedance performance of the battery cell are achieved.
Patent Information
- Application Number
- CN202510014005.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the condensed electrolyte active monomer inside the battery cell has insufficient reaction, high monomer residues, serious side reactions, and the conventional in-situ condensed electrolyte polymer matrix materials have poor temperature resistance and high glass transition temperature, resulting in less obvious improvement in cell safety performance and thermal runaway.
A wide-temperature domain gel nanoparticle emulsion is used to prepare gel nanoparticle precursors through emulsion polymerization, and are applied to the positive electrode, negative electrode or separator surface of the battery cell through spraying, roll coating, etc., forming a three-dimensional mesh connection state, improving the high-temperature resistance of the electrolyte and the ion transmission ability at low temperatures.
It significantly improves the safety performance and thermal stability of the battery cell, reduces the impedance and side reaction risks of the battery cell, and enhances the overall performance of the battery cell.
Smart Images

Figure CN119823313A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a technology for improving the surface of positive and negative electrodes or diaphragm coatings of battery cells. Background Art
[0002] With the rapid development of lithium-ion batteries and sodium-ion batteries, the energy density and single-cell capacity of battery cells are constantly increasing, and the resulting thermal runaway safety issues of lithium-ion batteries and sodium-ion batteries have become a major challenge facing the new energy industry. Therefore, the demand for high-safety lithium-ion batteries and sodium-ion batteries is increasing. Traditional lithium-ion batteries and sodium-ion batteries use high-temperature, easily shrinkable polyolefin diaphragms coated with inorganic oxide ceramics to improve their thermal shrinkage properties as diaphragm materials for lithium-ion batteries and sodium-ion batteries, and use flammable organic solvents and lithium salts or sodium salts as electrolytes for lithium-ion batteries and sodium-ion batteries. Therefore, due to the poor temperature resistance and easy shrinkage of the diaphragm and the easy combustion of the electrolyte, it is difficult to meet the needs of high-safety lithium-ion batteries and sodium-ion batteries. Among them, the flammable organic electrolyte has a low flash point, is easy to leak, is easy to gasify, and is easy to burn, which greatly increases the safety risks of the battery during use. Conventional ceramic-coated polyolefin diaphragms have low thermal shrinkage and melting temperatures of polyolefin-based films (around 130°C), and low softening temperatures of ceramic-coated adhesives (around 110°C), which lead to high-temperature shrinkage, film breakage, and easy breakage of the ceramic-coated diaphragm and ceramic layer. The above shortcomings of the diaphragm and electrolyte lead to frequent safety accidents of lithium-ion batteries and sodium-ion batteries. At present, in-situ condensed electrolytes can improve the safety performance of lithium-ion batteries and sodium-ion batteries while ensuring their electrical properties. The principle is that after the active monomers initiate polymerization inside the lithium-ion battery and sodium-ion battery, they form a three-dimensional network structure with the electrolyte to lock the organic electrolyte, making the electrolyte no longer fluid and forming a condensed electrolyte. Condensed electrolytes can effectively reduce the flash point of the electrolyte, prevent leakage, and make it difficult to gasify. At the same time, the three-dimensional network structure formed by the condensed electrolyte polymer matrix polymer bonds the diaphragm ceramic coating into an integral structure, and firmly bonds this integral structure ceramic coating to the surface of the electrode. In addition, the high temperature resistance of the three-dimensional network structure of the condensed electrolyte polymer avoids the breakage of the ceramic layer caused by the thermal shrinkage of the polyolefin diaphragm and the softening of the ceramic coating binder, thereby greatly improving the battery safety performance.
[0003] However, in the prior art, the in-situ condensed electrolyte has the following problems: 1. The process route of mixing with the electrolyte and injecting it into the battery cell and then heating to initiate polymerization leads to insufficient reaction of the active monomers of the condensed electrolyte inside the battery cell, a high monomer residual rate, and serious side reactions; 2. The conventional in-situ condensed electrolyte polymer matrix material has poor temperature resistance (softening at around 130°C), and has no obvious improvement on the thermal runaway of lithium-ion batteries and sodium-ion batteries; 3. The glass transition temperature of the condensed electrolyte polymer matrix material is relatively high, resulting in poor ionic conductivity of the condensed electrolyte.
[0004] More specifically, the prior art has the following problems:
[0005] 1. The condensed electrolyte is mixed with the electrolyte and injected into the battery cell. When it contacts the positive and negative electrodes and the surface of the diaphragm, it penetrates unevenly into the positive and negative electrodes. When the battery cell is subjected to the subsequent thermal polymerization process, the active monomers of the condensed electrolyte in the battery cell are not fully reacted, the residual rate of the uneven monomers is high, and the side reactions are serious;
[0006] 2. Conventional in-situ condensed electrolyte polymer matrix materials have poor temperature resistance (softening at around 130°C), and have little effect on improving thermal runaway of lithium-ion batteries and sodium-ion batteries;
[0007] 3. The glass transition temperature of the polymer matrix material of conventional condensed electrolytes is relatively high, resulting in greater resistance to the transport of lithium ions and sodium ions in conventional condensed electrolytes and between the "liquid / solid" interfaces, and greater cell impedance. Summary of the invention
[0008] Therefore, the technical problem to be solved by the present invention is:
[0009] 1. The active monomers of the condensed electrolyte inside the battery cell do not react fully, the monomer residual rate is high, the reaction products of the in-situ polymerization are unevenly distributed inside the battery cell, the side reactions are serious, and the battery cell polarization is large;
[0010] 2. The conventional in-situ condensed electrolyte polymer matrix material has poor temperature resistance (softening at around 130°C);
[0011] 3. During the embedding and extraction process of condensed electrolytes between the “liquid / solid” phases at low temperatures, the desolvation leads to the problem of high internal resistance.
[0012] In order to achieve the above-mentioned purpose, the present invention provides a wide temperature range gel nanoparticle emulsion, characterized in that the polymerization monomers used in the particle emulsion include a first monomer, a second monomer and a third monomer; wherein the first monomer is an acrylate monomer; the second monomer is a silicone-containing acrylate monomer; and the third monomer is a monomer containing silicone, acrylate and hydroxyl functional groups.
[0013] Preferably, the particle emulsion further comprises an initiator, an emulsifier, a buffer and a solvent;
[0014] The initiator is one or more water-soluble thermal decomposition type and redox type initiator;
[0015] The emulsifier is one or more of cationic, anionic, amphoteric and nonionic emulsifiers;
[0016] The buffer is a pH buffer;
[0017] The solvent is deionized water.
[0018] Preferably, the weight ratio of the components in the wide temperature range gel nanoparticle emulsion is:
[0019] The mass content of the first monomer is 10-40%; the mass content of the second monomer is 5-35%; the mass content of the third monomer is 5-25%; the mass content of the initiator is 0.01-5%; the mass content of the emulsifier is 0.5-10%; the mass content of the buffer is 0.5-10%; and the balance is solvent.
[0020] Exemplarily, the mass content of the first monomer in the wide temperature range gel nanoparticles can be 10%, 20%, 30%, or 40%; the mass content of the second monomer in the wide temperature range gel nanoparticles can be 5%, 10%, 20%, 30%, or 35%; the mass content of the third monomer in the wide temperature range gel nanoparticles can be 5%, 10%, 20%, 30%, or 35%; the mass content of the initiator in the wide temperature range gel nanoparticles can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 4%, or 5%; the mass content of the emulsifier in the wide temperature range gel nanoparticles can be 0.5%, 1%, 2%, 4%, 6%, 8%, or 10%; the mass content of the buffer in the wide temperature range gel nanoparticles can be 0.5%, 1%, 2%, 4%, 6%, 8%, or 10%; and the balance is solvent.
[0021] Preferably, the first monomer of the acrylic ester is one or more selected from the group consisting of methyl acrylate, ethyl acrylate, hexyl acrylate, butyl acrylate, isobutyl acrylate, methyl methacrylate, hexyl methacrylate, octyl methacrylate, trifluoroethyl methacrylate, stearic acid methyl methacrylate, benzyl acrylate, benzyl methacrylate, 2-phenoxyethyl methyl methacrylate, and hydroxymethyl acrylamide;
[0022] The second monomer containing silicone acrylate is one or more of 3-(trimethoxysilyl)propyl acrylate, 2-(trimethylsilylmethyl)ethyl acrylate, triisopropylsilyl acrylate, 3-(methoxydimethylsilyl)propyl acrylate, methacryloxypropyl tris(trimethylsiloxy)silane, and (3-acryloxypropyl)tris(trimethylsiloxy)silane;
[0023] The general structural formula of the third monomer containing silicon oxygen, acrylate and oxygen heterocyclic functional groups is:
[0024]
[0025] In the formula, R1 is -HC=CH2, -C(CH3)=CH1(CH2) n - one of CH3, where 0≤n≤6;
[0026] R2 is -[Si(CH3)2-O] x -, where 1≤x≤6;
[0027] R3 is R 3-1 , R 3-2 , R 3-3 , R 3-4 One of
[0028] R3 is one of the hydroxyl functional groups,
[0029] Where R 3-1 The structural formula is: -C3H5O
[0030] Where R 3-2 The structural formula is: -C4H7O
[0031] Where R 3-3 The structural formula is: -C2H4O
[0032] Where R 3-4 The structural formula is: -C5H9O;.
[0033] Preferably, the water-soluble thermal decomposition type and redox type initiator is one or more of potassium persulfate, sodium persulfate, hydrogen persulfide, isopropyl hydroperoxide, ammonium persulfate, tert-butyl hydroperoxide, and diisopropylbenzene hydroperoxide.
[0034] The cationic, anionic, amphoteric and nonionic emulsifiers are one or more of sodium dodecyl sulfonate, lithium dodecyl sulfate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, nonylphenol polyethylene oxide ether, alkylphenol polyoxyethylene ether (OP-10), YH-10, sodium p-styrene sulfonate, sodium vinyl sulfonate and sodium allyloxyhydroxypropane sulfonate.
[0035] The buffer is one or more of sodium bicarbonate, sodium dihydrogen phosphate and sodium acetate.
[0036] The solvent is deionized water.
[0037] The method for preparing the wide temperature range gel nanoparticle emulsion provided by the present invention comprises the following steps:
[0038] Step 1: Pre-emulsify emulsion A: add the solvent into a reaction kettle at 25°C and normal pressure, mechanically stir at 100-1500rpm, add the first monomer, the second monomer, the third monomer, the emulsifier, and the initiator in sequence, and mechanically stir for 30 minutes to obtain an egg white emulsion-like emulsion A;
[0039] Step 2: Preparation of a wide temperature range gel nanoparticle emulsion by emulsion polymerization: At 25°C and normal pressure, add the solvent into a reactor, mechanically stir at 100-1500rpm, heat to 30-60°C, add an emulsifier, an initiator, a buffer, and 2-30% of the pre-emulsified emulsion A in step 1 in sequence, heat to 50-90°C, keep warm for 0.1-1.5h, then add the remaining pre-emulsified emulsion A in step 1, and keep warm at 50-90°C for 1-6h to obtain a gel nanoparticle core emulsion.
[0040] The wide temperature range gel nanoparticle emulsion provided by the invention is used in combination with a positive electrode, a negative electrode, a separator and a solid electrolyte of a battery cell.
[0041] The prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in the positive and negative electrode slurries of the battery cell by drying into powder or directly adding the emulsion, and is uniformly distributed in the positive and negative electrodes of the battery cell through the battery cell manufacturing process of coating, drying and rolling;
[0042] The electrolyte is further injected through the battery cell, and under the action of liquid absorption, swelling and re-crosslinking of the gel nanoparticles, the positive electrode, negative electrode and the separator coated with the gel nanoparticles inside the battery cell form a three-dimensional network connection state.
[0043] The prepared gel nanoparticle emulsion is applied to the surface of the negative electrode by spraying or roller coating, and a separator coated with oxide ceramic and gel nanoparticles on one side or both sides is made into a battery cell;
[0044] Alternatively, the prepared gel nanoparticle emulsion is applied to the surface of the negative electrode sheet coated with the solid electrolyte by spraying or roller coating to prepare a battery cell;
[0045] Alternatively, the prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in a solid electrolyte slurry such as an oxide, sulfide, or halide by drying it into powder or directly adding the emulsion. The slurry is applied to the surface of the positive and negative electrodes of the battery cell and dried to form a mixed solid electrolyte layer to make a battery cell.
[0046] Application of the wide temperature range gel nanoparticle emulsion provided by the present invention:
[0047] Preferably, the composite separator for a battery cell comprises a separator and a gel nanoparticle emulsion coated on the separator.
[0048] Preferably, one side or both sides of the diaphragm have a functional coating; the gel nanoparticle emulsion is coated on the surface of the diaphragm and / or the functional coating;
[0049] The diaphragm is a porous polyolefin diaphragm;
[0050] The functional coating is micro-nano functional particles, and the micro-nano functional particles are one or more of lithium alumina, boehmite, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium aluminum titanium phosphate, lithium lanthanum tantalum oxide, and germanium aluminum phosphate;
[0051] The method for preparing the composite diaphragm provided by the present invention comprises the following steps:
[0052] Step 1: obtaining gel nanoparticle emulsion;
[0053] Step 2: using any of the following coating methods: spraying, spot coating, dip coating, air knife coating, blade coating, roller coating, roller coating, gravure coating, slit coating, multilayer slide coating, curtain coating, spin coating, coating the obtained gel nanoparticle emulsion onto the surface of the diaphragm base film and / or the diaphragm functional coating, and heating and drying to obtain a composite diaphragm;
[0054] Wherein, in step 2, the drying temperature is 40-90° C., and the drying time is 1-10 min.
[0055] Through the above methods, a variety of coating methods are provided, that is, the particle emulsion obtained by the present invention is coated on the surface of the positive electrode, the negative electrode or the separator in different forms.
[0056] The beneficial effects of the present invention are:
[0057] 1. On the outside of lithium-ion batteries and sodium-ion batteries, an emulsion-state gel nanoparticle precursor is first prepared by emulsion polymerization, and then coated on the surface of a polyolefin diaphragm or a polyolefin diaphragm coated with a metal oxide ceramic layer by spraying, roller coating, etc., to solve the problems of insufficient reaction of active monomers of conventional in-situ condensed electrolytes, high monomer residual rate, and serious side reactions;
[0058] 2. In the synthesis of gel nanoparticle emulsion, silicon-oxygen acrylate monomers and silicon-oxygen, acrylate and oxygen-containing heterocyclic functional group monomers are introduced to improve the high temperature resistance of condensed electrolytes, thereby improving the safety performance of lithium-ion batteries and sodium-ion batteries. At the same time, the glass transition temperature of condensed electrolyte polymers is reduced to further reduce the impedance of ion embedding and extraction at the "liquid / solid" interface of the condensed electrolyte at low temperatures, thereby improving the charge and discharge performance of the battery cell at low temperatures.
[0059] 3. The prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in the positive and negative electrode slurries of the battery cell by drying into powder or directly adding the emulsion. The emulsion is uniformly distributed in the positive and negative electrodes of the battery cell through battery cell manufacturing processes such as coating, drying, and rolling. The electrolyte is injected through the battery cell. Under the action of liquid absorption, swelling, and re-crosslinking of the gel nanoparticles, the positive electrode, the negative electrode, and the diaphragm coated with the gel nanoparticles inside the battery cell form a three-dimensional network gel connection state, thereby building an excellent ion transmission channel, reducing the desolvation energy barrier of the ions, and then achieving low impedance of the battery cell; in the formed battery cell structure, the positive electrode or the negative electrode is in contact with the diaphragm, and the positive electrode, the negative electrode and the diaphragm are Gel nanoparticles can be coated on all surfaces. These particles contain materials required for emulsion reaction. Therefore, when they reach a certain temperature after contact, they will react with each other to undergo polymerization and cross-linking, thereby forming a three-dimensional network gel connection state, thus building an excellent ion transmission channel. At the same time, when the battery cell thermal runaways, the gel nanoparticles will further polymerize into a film at high temperature, which can wrap and restrain the positive electrode material, negative electrode material and metal oxide ceramic material of the ceramic diaphragm, thereby inhibiting the chain reaction of the positive and negative electrodes under thermal runaway of the battery cell and the thermal shrinkage of the diaphragm, further inhibiting the heat diffusion inside the battery cell, improving the overall thermal stability of the battery cell, and improving the safety of the battery cell as a whole.
[0060] 4. The prepared gel nanoparticle emulsion is applied to the surface of the negative electrode by spraying or roller coating, and is made into a battery cell with a separator coated with oxide ceramics and gel nanoparticles on one or both sides, thereby achieving the effect of improving the internal interface bonding ability of the battery cell and improving safety;
[0061] 5. The prepared gel nanoparticle emulsion is applied to the surface of the negative electrode sheet coated with the solid electrolyte by spraying or roller coating to make a battery cell. The good liquid absorption ability and high-temperature film-forming characteristics of the gel nanoparticles can protect the integrity of the solid electrolyte layer under high-temperature thermal runaway of the battery cell, thereby isolating the positive and negative electrodes from short-circuit contact, thereby eliminating the traditional polyolefin separator of the battery cell and realizing the "separator-free" battery cell, which significantly reduces the cost of the battery cell while ensuring the performance of the battery cell;
[0062] 6. The prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in a solid electrolyte slurry such as an oxide, sulfide, or halide by drying it into powder or directly adding the emulsion. The slurry is applied to the surface of the positive and negative electrodes of the battery cell and dried to form a mixed solid electrolyte layer to make a battery cell. After the battery cell is injected with liquid, a mixed electrolyte structure of a condensed state and a solid state is formed inside the battery cell, thereby solving the interface contact problem of the solid electrolyte and the low ion conductivity, while improving the thermal stability and safety of the battery cell.
[0063] 7. The wide temperature range gel nanoparticle emulsion provided by the present invention can be used in combination with the positive electrode, negative electrode, separator, and solid electrolyte of the battery cell, and the adding method can be varied. For example, it can be added to the slurry before the existing positive electrode and negative electrode are made to form an electrode; or a layer of particle emulsion can be coated on the surface of the already formed positive electrode, negative electrode, or separator; in addition, the solid electrolyte can also be mixed or combined with the particle emulsion for use. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0065] Figure 1 It is the DSC curve change diagram of the control group and the embodiment (experimental group);
[0066] Figure 2 is a graph of low temperature impedance change of the control group and the embodiment (experimental group);
[0067] Figure 3 It is a statistical diagram of discharge capacity at room temperature in an embodiment of the present invention.
[0068] Figure 4 It is a statistical diagram of the first charge and discharge efficiency in the embodiment of the present invention.
[0069] Figure 5 It is a statistical diagram of the charge and discharge capacity retention rate of the embodiment of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0071] Embodiment 1:
[0072] At 25°C and normal pressure, 1000.0 g of deionized water was added to a reaction kettle, mechanically stirred at 500 rpm, and 1000.0 g of ethyl acrylate, 500.0 g of 2-(trimethylsilylmethyl)ethyl acrylate, 500.0 g of dimethylsiloxane glycidyl acrylate, 0.5 g of ammonium persulfate, 20 g of sodium dodecyl sulfate, and 20 g of sodium bicarbonate were added in sequence, and mechanically stirred for 30 min to obtain an egg white emulsion-like emulsion A;
[0073] At 25°C and normal pressure, 6899.0g of deionized water was added to a reactor, mechanically stirred at 500rpm, heated to 30°C, 0.5g of ammonium persulfate, 30g of sodium dodecyl sulfate, and 30g of sodium bicarbonate were added in sequence, and stirred for 10min, then 20% by weight of the above emulsion A was added to the reactor at a rate of 17.5g / min, and heated to 80°C at a heating rate of 5.0°C / min. After the temperature reached 80°C, the reaction was kept warm for 0.5h, and then the remaining emulsion A was added, and the reaction was kept warm at 80°C for 2h; a wide temperature range gel nanoparticle emulsion was obtained;
[0074] After drying the emulsion, the dried polymer was obtained and the softening temperature was tested by DSC. Figure 1 As shown, compared with the softening temperature of the control group (Tg = 85°C), the experimental group exhibits a significantly lower softening temperature (Tg = 15°C); this indicates that the Tg of the polymer obtained in the embodiment of the present invention has been significantly reduced. The material used in the control group is polymethyl methacrylate (PMMA).
[0075] The process of applying the emulsion to the composite diaphragm of the battery cell is as follows:
[0076] The wide temperature range gel nanoemulsion is coated onto the surface of the diaphragm ceramic coating by roller coating, and heated and dried at 60° C. to obtain a composite diaphragm.
[0077] The composite diaphragm is made into a battery cell and the low temperature impedance of the battery cell is tested. Figure 2 As shown, compared with the PVDF diaphragm cell impedance of the control group, the diaphragm cell impedance of the experimental group (this embodiment) is significantly reduced.
[0078] Example 2
[0079] At 25°C and normal pressure, 1500.0 g of deionized water was added to a reaction kettle, mechanically stirred at 500 rpm, and 2500.0 g of ethyl acrylate, 1000.0 g of 2-(trimethylsilylmethyl)ethyl acrylate, 1000.0 g of dimethylsiloxane glycidyl acrylate, 1.0 g of ammonium persulfate, 40 g of sodium dodecyl sulfate, and 40 g of sodium bicarbonate were added in sequence, and mechanically stirred for 30 min to obtain an egg white emulsion-like emulsion A;
[0080] At 25°C and normal pressure, 3798.0g of deionized water was added to a reactor, mechanically stirred at 500rpm, heated to 30°C, 1g of ammonium persulfate, 60g of sodium dodecyl sulfate, and 60g of sodium bicarbonate were added in sequence, and stirred for 10min. Subsequently, 25% by weight of the above emulsion A was added to the reactor at a rate of 50.0g / min, and the temperature was simultaneously heated to 80°C at a heating rate of 5.0°C / min. After the temperature reached 80°C, the reaction was kept warm for 1.0h; then the remaining emulsion A in step 1 was added, and the reaction was kept warm at 80°C for 4h to obtain a wide temperature range gel nanoparticle emulsion;
[0081] The process of applying the processed emulsion to the composite diaphragm of the battery cell is as follows:
[0082] The above-mentioned wide temperature range gel nanoparticle emulsion was coated on the surface of the ceramic diaphragm and the surface of the negative electrode of the battery cell by roller coating, and heated and dried at 60°C to obtain a composite diaphragm and a coated negative electrode, and then made into a battery cell. The capacity, initial charge and discharge efficiency and -10°C charge and discharge performance of the battery cell were compared with the battery cell made of a composite diaphragm coated with PVDF. The specific test data are as follows: Figures 3 to 5 As shown. Figure 3 As can be seen, the discharge capacities of the two control PVDF groups are 9.368 and 9.371, respectively, while the discharge capacities of the two experimental groups of this embodiment are 9.695 and 9.717, respectively, which indicates that the discharge capacity of this embodiment is significantly better than that of the control group.
[0083] Figure 4 In the first charge and discharge efficiency, the capacity efficiencies of the two control PVDF groups were 83.79 and 83.91 respectively, while the capacity efficiencies of the experimental group of this embodiment were 86.08 and 86.14 respectively, which indicates that the capacity efficiency of this embodiment is better than that of the control group.
[0084] Figure 5 In the charge and discharge capacity retention efficiency test, the charge and discharge efficiencies of the two control PVDF groups were 79.61 and 77.08 respectively, while the charge efficiency of the experimental group of this embodiment reached 84.23 and 84.16; in addition, the discharge efficiencies of the two control PVDF groups were 83.30 and 81.01 respectively, while the discharge efficiency of the experimental group of this embodiment reached 87.45 and 87.32. This shows that the charge and discharge capacity retention efficiency of this embodiment is better than that of the control group.
[0085] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A wide temperature range gel nanoparticle emulsion, characterized in that: The polymerizable monomers used in the particle emulsion include a first monomer, a second monomer and a third monomer; wherein the first monomer is an acrylate monomer; the second monomer is a silicone-containing acrylate monomer; and the third monomer is a monomer containing silicone, acrylate and hydroxyl functional groups.
2. The wide temperature range gel nanoparticle emulsion according to claim 1, characterized in that: The particle emulsion also includes an initiator, an emulsifier, a buffer and a solvent; The initiator is one or more water-soluble thermal decomposition type and redox type initiator; The emulsifier is one or more of cationic, anionic, amphoteric and nonionic emulsifiers; The buffer is a pH buffer; The solvent is deionized water.
3. The wide temperature range gel nanoparticle emulsion according to claim 2, characterized in that: The weight proportions of the components in the wide temperature range gel nanoparticle emulsion are as follows: the mass content of the first monomer is 10-40%; the mass content of the second monomer is 5-35%; the mass content of the third monomer is 5-25%; the mass content of the initiator is 0.01-5%; the mass content of the emulsifier is 0.5-10%; the mass content of the buffer is 0.5-10%; and the balance is the solvent.
4. The wide temperature range gel nanoparticle emulsion according to claim 3, characterized in that: The first monomer of the acrylic ester is one or more of methyl acrylate, ethyl acrylate, hexyl acrylate, butyl acrylate, isobutyl acrylate, methyl methacrylate, hexyl methacrylate, octyl methacrylate, trifluoroethyl methacrylate, stearic acid methyl methacrylate, benzyl acrylate, benzyl methacrylate, 2-phenoxyethyl methyl methacrylate, and hydroxymethyl acrylamide; The second monomer containing silicone acrylate is one or more of 3-(trimethoxysilyl)propyl acrylate, 2-(trimethylsilylmethyl)ethyl acrylate, triisopropylsilyl acrylate, 3-(methoxydimethylsilyl)propyl acrylate, methacryloxypropyl tris(trimethylsiloxy)silane, and (3-acryloxypropyl)tris(trimethylsiloxy)silane; The general structural formula of the third monomer containing silicon oxygen, acrylate and oxygen heterocyclic functional groups is: In the formula, R1 is -HC=CH2, -C(CH3)=CH1(CH2) n - one of CH3, where 0≤n≤6; R2 is -[Si(CH3)2-O] x -, where 1≤x≤6; R3 is one of the hydroxyl functional groups, Where R 3-1 The structural formula is: -C3H5O Where R 3-2 The structural formula is: -C4H7O Where R 3-3 The structural formula is: -C2H4O Where R 3-4 The structural formula is: -C5H9O; The water-soluble thermal decomposition type and redox type initiator is one or more of potassium persulfate, sodium persulfate, hydrogen persulfide, isopropyl hydroperoxide, ammonium persulfate, tert-butyl hydroperoxide, and diisopropylbenzene hydroperoxide; The cationic, anionic, amphoteric and nonionic emulsifiers are one or more of sodium dodecyl sulfonate, lithium dodecyl sulfate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, nonylphenol polyoxyethylene ether, alkylphenol polyoxyethylene ether (OP-10), YH-10, sodium p-styrene sulfonate, sodium vinyl sulfonate and sodium allyloxyhydroxypropane sulfonate; The buffer is one or more of sodium bicarbonate, sodium dihydrogen phosphate, and sodium acetate; The solvent is deionized water.
5. The method for preparing a wide temperature range gel nanoparticle emulsion according to any one of claims 1 to 4, characterized in that: The following steps are included: Step 1: Pre-emulsified emulsion A: Add the solvent into a reaction kettle at 25°C and normal pressure, mechanically stir at 100-1500rpm, add the first monomer, the second monomer, the third monomer, the emulsifier, and the initiator in sequence, and mechanically stir for 30 minutes to obtain an egg white emulsion-like emulsion A, i.e., pre-emulsified emulsion A; Step 2: Preparation of a wide temperature range gel nanoparticle emulsion by emulsion polymerization: At 25°C and normal pressure, add the solvent into a reactor, mechanically stir at 100-1500rpm, heat to 30-60°C, add an emulsifier, an initiator, a buffer, and 2-30% of the pre-emulsified emulsion A in step 1 in sequence, heat to 50-90°C, keep warm for 0.1-1.5h, then add the remaining pre-emulsified emulsion A in step 1, and keep warm at 50-90°C for 1-6h to obtain a gel nanoparticle core emulsion.
6. The use of the wide temperature range gel nanoparticle emulsion according to any one of claims 1 to 4, characterized in that: The wide temperature range gel nanoparticle emulsion is used in combination with the positive electrode, the negative electrode, the separator and the solid electrolyte of the battery cell.
7. The use of the wide temperature range gel nanoparticle emulsion according to claim 6, characterized in that: The prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in the positive and negative electrode slurries of the battery cell by drying into powder or directly adding the emulsion, and is uniformly distributed in the positive and negative electrodes of the battery cell through the battery cell manufacturing process; The electrolyte is further injected through the battery cell, and under the action of liquid absorption, swelling and re-crosslinking of the gel nanoparticles, the positive electrode, negative electrode and the separator coated with the gel nanoparticles inside the battery cell form a three-dimensional network connection state.
8. The use of the wide temperature range gel nanoparticle emulsion according to claim 6, characterized in that: The prepared gel nanoparticle emulsion is applied to the surface of the negative electrode by spraying or roller coating, and a separator coated with oxide ceramic and gel nanoparticles on one side or both sides is made into a battery cell; The prepared gel nanoparticle emulsion is applied to the surface of the negative electrode sheet coated with the solid electrolyte by spraying or roller coating to prepare a battery cell; The prepared gel nanoparticle emulsion is uniformly dissolved or dispersed in the solid electrolyte slurry by drying into powder or directly adding the emulsion. The slurry is coated on the surface of the positive and negative electrodes of the battery cell and dried to form a mixed solid electrolyte layer to make a battery cell.
9. The use of the wide temperature range gel nanoparticle emulsion according to claim 6, characterized in that: One side or both sides of the diaphragm have a functional coating; the gel nanoparticle emulsion is coated on the surface of the diaphragm and / or the functional coating; The diaphragm is a porous polyolefin diaphragm; The functional coating is micro-nano functional particles, and the micro-nano functional particles are one or more of lithium aluminum oxide, boehmite, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium aluminum titanium phosphate, lithium lanthanum tantalum oxide, and germanium aluminum phosphate.
10. The use of the wide temperature range gel nanoparticle emulsion according to claim 9, comprising the following steps: Step 1: obtaining gel nanoparticle emulsion; Step 2: using any of the following coating methods: spraying, spot coating, dip coating, air knife coating, blade coating, roller coating, roller coating, gravure coating, slit coating, multilayer slide coating, curtain coating, spin coating, coating the gel nanoparticle emulsion onto the surface of the diaphragm and / or the diaphragm functional coating, and heating and drying to obtain a composite diaphragm; Wherein, in step 2, the drying temperature is 40-90° C., and the drying time is 1-10 min.
Citation Information
Patent Citations
Epoxy organosilicone ultraviolet curing coating modified by (methyl) acrylic acid and preparation method thereof
CN101555386A
Epoxy and acrylic acid hybrid emulsion, and preparation method and application thereof
CN106519528A
Organic silicon modified acrylic emulsion and preparation method thereof
CN108359046A
Adhesive for silicon-carbon negative electrode of lithium ion battery, and preparation and application of adhesive
CN110364735A
Preparation method of novel epoxy silicone oil modified acrylate anti-doodling emulsion
CN111607092A